The “As If” Business Internship: An Instructional Response to Extenuating Circumstances - Wilson, Asa; Chowdhury, Sabit; Nowak, Albert (Archives of Business Research, 2021)
An internship, especially in applied business disciplines, is an important experiential learning bridge from the academy to further training and/or a career threshold. The Covid-19 outbreak frustrated student placement opportunities in settings with a high exposure risk. The pandemic also disrupted degree progress and graduation targets for many. A case example of an alternative to an on-site internship is described that is a response to Covid-19 limitations. This alternative is defined as the “As-If” internship because it captures several learning outcomes of a facility placement. On-site internship success factors and benefits are discussed as a benchmark for demonstrating how the “As-If” experience fulfills on-site learning objectives. The alternative is further discussed as an approach for other extenuating circumstances.